Listeria monocytogenes that lyse in the macrophage cytosol trigger AIM2-mediated pyroptosis - Sauer, John-Demian (2010)
To gain insight into the mechanisms by which host cells detect cytosolic invasion by intracellular pathogens, a genetic screen was performed to identify Listeria monocytogenes mutants that induced altered levels of host cell death. A mutation in lmo2473 resulted in hyper-stimulation of host cell death and IL-1β secretion (pyroptosis) following bacteriolysis in the macrophage cytosol. In addition, strains engineered to lyse in the cytosol by expression of both bacteriophage holin and lysin or induced to lyse by treatment with ampicillin stimulated pyroptosis. Pyroptosis was independent of the Nlrp3 and Nlrc4 receptors, but dependent on ASC and AIM2. Importantly, wild type L. monocytogenes were also found to lyse, albeit at low levels, and trigger AIM2-dependent pyroptosis. Since AIM2 is activated by DNA, these data suggested that pyroptosis is triggered by bacterial DNA released during lysis.